2020
DOI: 10.1021/acsomega.9b03922
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetics of Lamivudine and Its Interaction with Schisandra chinensis Extract in Rats

Abstract: Schisandra chinensis (Turcz.) Baill. (S. chinensis) extract and its active ingredient, schizandrin, have been used as a botanical medicine and dietary supplement for the treatment of hepatitis. Lamivudine is an antiretroviral drug and is used to treat hepatitis B viral infection. The aim of this study was to develop an ultrahigh-performance liquid chromatography−tandem mass spectrometry (UHPLC−MS/MS) method for the measurement of lamivudine and to determine the pharmacokinetic behaviors of an aqueous−ethanol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Rats were dosed with 10 mg/kg NBMPR-P, the phosphorylated prodrug of NBMPR, or vehicle 20 minutes before 10 mg/kg clofarabine, 10 mg/kg lamivudine, or vehicle dosing. These clofarabine and lamivudine doses were sufficient to detect within the testes and were well-within the dose ranges of previously published studies (Arthaud and Seals, 2007;Bonate et al, 2005;Li et al, 2020;U.S. Food and Drug Administration, 2003;U.S.…”
Section: Rodent Modelssupporting
confidence: 84%
“…Rats were dosed with 10 mg/kg NBMPR-P, the phosphorylated prodrug of NBMPR, or vehicle 20 minutes before 10 mg/kg clofarabine, 10 mg/kg lamivudine, or vehicle dosing. These clofarabine and lamivudine doses were sufficient to detect within the testes and were well-within the dose ranges of previously published studies (Arthaud and Seals, 2007;Bonate et al, 2005;Li et al, 2020;U.S. Food and Drug Administration, 2003;U.S.…”
Section: Rodent Modelssupporting
confidence: 84%
“…Baill is cultivated in northeastern China, Korea, and Japan. As a traditional Chinese herb, it has been used as an antitussive and for the treatment of insomnia and hepatitis 18–20 . Recent studies have shown that the extracts of Schisandra possess biological activities, including anticancer, antioxidant, neuroprotective, hepatoprotective and anti‐inflammatory activities 21 .…”
Section: Introductionmentioning
confidence: 99%
“…As a traditional Chinese herb, it has been used as an antitussive and for the treatment of insomnia and hepatitis. 18 , 19 , 20 Recent studies have shown that the extracts of Schisandra possess biological activities, including anticancer, antioxidant, neuroprotective, hepatoprotective and anti‐inflammatory activities. 21 In addition, studies have reported that the Schisandra leaf extract relieves pain and inflammation in a rat model of OA.…”
Section: Introductionmentioning
confidence: 99%